2011
DOI: 10.2214/ajr.09.3302
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Clinical Significance of Noncardiac Findings on Cardiac MRI

Abstract: NCFs are commonly encountered on cardiac MRI studies, many of which are clinically relevant. Proper recognition of NCFs is critical to the comprehensive management of patients referred for cardiac MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
49
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 23 publications
3
49
4
Order By: Relevance
“…As far as defining the extent of major and significant findings, we found the definitions in the study published by Atalay et al, 6 as satisfactory for the purposes of our study. Major findings according to our study were those that were important enough to warrant highlighting to the clinical team but not always causing delay or cancellation of AAA repair.…”
Section: Discussionsupporting
confidence: 65%
“…As far as defining the extent of major and significant findings, we found the definitions in the study published by Atalay et al, 6 as satisfactory for the purposes of our study. Major findings according to our study were those that were important enough to warrant highlighting to the clinical team but not always causing delay or cancellation of AAA repair.…”
Section: Discussionsupporting
confidence: 65%
“…These findings are in accordance with the study of McKenna et al [12], which demonstrated the importance of reviewing the scout sequences that identified the ECF most frequently. Another recent study identified SSFP scout images and axial T1-weighted thoracic fast spin-echo images as being most useful, detecting 95% of all noncardiac findings [13], whereas Atalay et al found axial bright-blood and dark-blood imaging to have the highest detection rates for ECF [15]. There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 71%
“…These two modalities are difficult to compare as MRI has lower spatial resolution, meaning that the pickup of smaller lesions is more challenging. 2 One study compared the two in the same patient cohort and found a prevalence of 5% when CT was carried out and 2% on MRI. 4 Despite this study being carried out on an HIV-positive cohort we found a lower prevalence in this study compared to studies in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is noteworthy that this study was carried out on well, asymptomatic patients for research purposes, whereas six out of the seven previously published studies have looked for CSECFs in patients having clinically indicated MRI scans. 2,3,[5][6][7][8] In some instances these patients were intubated, which would increase the chance of finding pathology such as atelectasis, pleural effusions and pneumonias which were often the most common findings. Dewey et al 4 found a prevalence of 2% CSECFs in a research group of older patients, mean age 63 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation